Use of isotopic tungsten tracers and a stable-isotope-mixing model to characterize divertor source location in the DIII-D metal rings campaign. (May 2019) - Unterberg, E.A.; Donovan, D.C.; Duran, J.D.; Stangeby, P.C.; Zamperini, S.; Abrams, T.; Rudakov, D.L.; Wampler, W.R.; Zach, M.P.
Highlights: A basic model is presented that aided the first-time use of isotopic W tracers in a fusion device. Using the model, upstream probe deposition shows that the W sources follow strike-point position. Isotopic signatures have asymmetric deposition patterns on opposite sides of the upstream probe. Abstract: A basic stable isotope mixing model (bSIMM) is presented that enables the first-time use of multiple isotopic tungsten (W) tracers in a fusion device. DIII-D installed two toroidally symmetric, but poloidally distinct, arrays of tiles in the outer region of the lower divertor that are each distinguishable by different stable-isotope signatures of W. This installation was called the metal rings campaign. Experiments were then carried out with this setup to assess the W source from each location and how the sourced W led to contamination of the main scrape-off layer (SOL). The bSIMM method is derived and shown to be in good agreement with benchmark tests using known mixtures of different isotopic W signatures. The method is applied to a set of dual-facing impurity Collector Probes (CP) exposed in H-mode discharges during this metal rings campaign. Using the bSIMM as the main analysis tool, CP radial profiles show that the divertor W sources follow the discharge's strike-point position. In addition, opposing faces of the CPs have different W deposition profiles indicating poloidal variation of W content in the SOL and the isotopic signatures are shown to follow these trends. This work demonstrates that this methodology for detecting isotopic W sourced from different plasma facing components in a fusion device is reliable and versatile.